Optimalisasi Pengelolaan Sampah untuk Potensi Ekonomi melalui Workshop Lingkungan di Desa Mandiri Banyurejo - Yutta Vemin Hanafi; Bondan Megantoro; Fransiska Dabi; Chandra Pratama; Fransiskus F.H. Thoba; Petronela Solossa; Moch G. A.A. Ari; Achmad M. Gyiansyah; Norbertus Klau; Rachmadhani R. Herlansyah (Lembaga Pengembangan Kinerja Dosen, 2025)
The Community Service Program (KKN) is an intracurricular activity that is mandatory for students as a form of community service. In this context, the KKN group R1 of Janabadra University Yogyakarta conducted a service activity in Banyurejo Village, Yogyakarta City, for six weeks. This activity carried the main theme of community empowerment in environmental management, with a primary focus on increasing awareness of the economic potential of waste through the implementation of an Environmental Workshop with the theme